Evaluasi Program Ekstrakurikuler Pramuka Sekolah Menengah Kejuruan - Heni Triana; - Wasitohadi; Bambang Ismanto (Universitas Kristen Satya Wacana, 2020)
The purpose of this study was to evaluate the scout extracurricular program at SMK Telekomunikasi Tunas Harapan. This research is included in qualitative evaluative research with Kirkpatrick's evaluation model which consists of four stages, namely: reaction, learning, behavior and results. The research subjects included 1 principal, 2 scout coaches, 4 teachers, and 77 class X students. Data collection techniques were through filling out questionnaires, observation, interviews, and documentation study. The stages taken in the data analysis process include: data collection, data reduction, drawing conclusions, data presentation. The data validation used triangulation of data sources and triangulation of data collection techniques. The results of this study indicate that: (1) at the reaction evaluation stage with a percentage of 87.88% included in the